Composition of legume soaking water and emulsifying properties in gluten-free bread. (April 2018) - Huang, San; Liu, Yuling; Zhang, Weihan; Dale, Kylie J; Liu, Silu; Zhu, Jingnan; Serventi, Luca
Soaking of legumes results in the loss of macronutrients, micronutrients and phytochemicals. Fibre, protein and phytochemicals found in legumes exert emulsifying activity that may improve the structure and texture of gluten-free bread. The legume soaking water of haricot beans, garbanzo chickpeas, whole green lentils, split yellow peas and yellow soybeans were tested in this study for functional properties and use as food ingredients. Composition, physicochemical properties and effect on the quality of gluten-free bread were determined for each legume soaking water. Haricot beans and split yellow peas released the highest amount of solids in the legume soaking water: 1.89 and 2.38 g/100 g, respectively. Insoluble fibre was the main constituent of haricot beans legume soaking water, while water-soluble carbohydrates and protein were the major fraction of split yellow peas. High quantities of phenolics (∼400 µg/g) and saponins (∼3 mg/g) were found in the legume soaking water of haricot beans, whole green lentils and split yellow peas. High emulsifying activity (46 and 50%) was found for the legume soaking water of garbanzo chickpeas and split yellow peas, probably due to their protein content and high ratio of water-soluble carbohydrates to dry matter. Such activity resulted in softer texture of the gluten-free bread. A homogeneous structure of crumb pores was found for split yellow peas, opposing that of whole green lentils. A balance between the contents of yeast nutrients and antinutrients was the likely basis of the different appearances.